2019
DOI: 10.1016/j.celrep.2019.08.085
|View full text |Cite
|
Sign up to set email alerts
|

PINK1/Parkin Influences Cell Cycle by Sequestering TBK1 at Damaged Mitochondria, Inhibiting Mitosis

Abstract: SUMMARY PINK1 and Parkin are established mediators of mitophagy, the selective removal of damaged mitochondria by autophagy. PINK1 and Parkin have been proposed to act as tumor suppressors, as loss-of-function mutations are correlated with enhanced tumorigenesis. However, it is unclear how PINK1 and Parkin act in coordination during mitophagy to influence the cell cycle. Here we show that PINK1 and Parkin genetically interact with proteins involved in cell cycle regulation, and loss of PINK1 and Parkin acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 58 publications
(84 reference statements)
2
84
0
Order By: Relevance
“…With regard to TBK1, it has been proven that TBK1 takes part in modulating cell growth and autophagy [43]. Moreover, Sarraf et al [44] also indicated that TBK1 exerted an important role in mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to TBK1, it has been proven that TBK1 takes part in modulating cell growth and autophagy [43]. Moreover, Sarraf et al [44] also indicated that TBK1 exerted an important role in mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk for Parkinson's disease has been associated with mutations in SNCA, PARK2 (parkin), PINK1, DJ-1, and LRRK2 which have been linked to mitochondrial function and oxidative stress (Yan et al, 2012). PINK1 and parkin mediates clearance of damaged mitochondria by mitophagy and may therefore influence mitotic cell cycle progression (Sarraf et al, 2019). PINK1 also regulates both retrograde and anterograde axonal transport of mitochondria via axonal microtubules (Liu et al, 2012) The interaction between PINK1 and parkin is likely involved in mitochondrial quality control mechanisms, where anterograde transport of damaged mitochondria is reduced and retrograde transport is enhanced for elimination by mitophagy in the neuronal cell body (Lionaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq analysis revealed no difference in the pattern of gene expression between WT and AMPK-KO Th cells recovered at the end of a 14-day culture with DCs and IL-7 (Supplemental Turnover of damaged mitochondria is part of the mitochondrial quality control process and it has recently been shown that enhanced mitophagy can slow-down the cell cycle progression (21). To measure mitochondria turnover in IL-7-treated WT and AMPK-KO Th cell cultures, we pulsed-chased mitochondria with the Mito-Green Tracker probe and followed the Mito-Green loss over time.…”
Section: Ampk Regulates Mitochondrial Fitness In T Cellsmentioning
confidence: 99%